Worlds at Play: Space and Player Experience in Fantasy Computer Games - Toft-Nielsen Claus (Nordicom Review, 2020)
The relationship between the fantasy genre and the medium of computer games has always been a very tight-knit one. The present article explores the close connection between fantasy and computer games through different media, arguing that the fantasy genre's specific ‘mode of function’ is the ability to build complete fictional worlds, whereby it creates specific experiences for its users. Based on empirical data from focus group interviews with players of the most popular Western Massively Multiplayer Online Role-Playing Game (MMORPG) of all times, World of Warcraft, the article develops the concept of worldness as an experiential, phenomenological understanding of player experience. I discuss how this way of framing a core quality of the fantasy genre (of world-building) functions across single fictional universes and aims to grasp a specific fantasy experience of being in the world. This experience works on the level of genre, by anchoring the specific fantasy world in the larger, surrounding fantasy genre matrix.